The Catholic Laity and the Development of Catholic Identity (discussiedossier over Catholic Identity and the Revolt of the Netherlands, 1520-1635) - M.R. Forster (BMGN: Low Countries Historical Review, 2011)
Pollmann, Judith, Catholic Identity and the Revolt of the Netherlands 1520-1635 (Past and Present; Oxford: Oxford University Press, 2011, xiv + 239 blz., ISBN 978 0 19 960991 8).